Plastics water storage module with filtering capability - ZHAO ZHENGPING; LYU GUOQING (2018)
The utility model discloses a plastics water storage module with filtering capability, including roof and bottom plate, roof and bottom plate and four curb plate form a rectangle hollow structure, thelast surface array of roof are equipped with the fixed slot, and the fixed slot joint has a top cap, the fixed slot is connected with the macrostoma end of funnel, goes up the vertical inside that extends to the rectangle structure of funnel, and the osculum end of going up the funnel is connected with the osculum end of funnel down, and the upper strata of going up the funnel inside is equippedwith the bars that permeate water, and the active carbon is installed to the below of the bars that permeate water, and the active carbon osculum that extends to down the funnel holds inside, the oneend bottom of funnel osculum end was provided with the filter screen under the active carbon was located, and lower funnel internally mounted has the micropore ceramic filter core. The utility model discloses effectively the im